(3GdEMSGf aj ONhd eedcI Gdjef JMJ Xd YOGdI Bd YKeGfs - (3TeS GdOjf YHO GdUeO Hf ESeGYjd Hf YHO GdUeO GdefRdj, GdehRYj,J (B1031 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Gbdje Gdjef GdeHGQc Gbdje jef hEjeGf TgO HPdc eG hQO ai HYV GdCNHGQ s
(3BNQgG (B:s
(3hGdGeGf GdGYQGV YeG ajg ef GdMcGjGJ GSde ddGYQGV aEf fLO YjHkG aSO GdNdd aGSJQ GNjc JSJQ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B10s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B5 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs